2020
DOI: 10.1186/s12889-020-09531-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of temperature variability on childhood allergic rhinitis in a subtropical city of China

Abstract: Background Many studies have shown an association of childhood respiratory diseases with short-term temperature variability such as diurnal temperature range (DTR) and temperature change between two neighboring days (TCN). However, the impact of temperature variability on allergic rhinitis (AR) has not been investigated so far. This study sought to evaluate the short-term effect of temperature variability (i.e., TCN and DTR) on AR, as well as to identify vulnerable subpopulations. Method We collected daily d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The results of this study showed that the risk of AR incidence elevated with the increase in air temperature in spring. However, another study provided evidence of a negative effect of abrupt temperature drops between two adjacent days on childhood AR ( 40 ). Further investigations to compare the effects of climate change on AR in different seasons might be needed.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that the risk of AR incidence elevated with the increase in air temperature in spring. However, another study provided evidence of a negative effect of abrupt temperature drops between two adjacent days on childhood AR ( 40 ). Further investigations to compare the effects of climate change on AR in different seasons might be needed.…”
Section: Discussionmentioning
confidence: 99%
“…1 Almost 600 million suffer from allergic rhinitis globally. 2 It is estimated that nearly 150 million are patients of allergic rhinitis in the Asia-Pacific region. 3 Reported incidence of allergic rhinitis in India ranges between 20% and 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for AR mainly include genetic factors (Kim et al 2012) and environmental factors, such as meteorological factors (Gao et al 2021;Hu et al 2020;Kim et al 2018), air pollution (Hu et al 2020;Lin et al 2021), and indoor allergens (Kim et al 2012). Recently more attention has been paid to the impacts of temperature in the process of AR (Carreras et al 2015;Gao et al 2021;Kim et al 2018;Wang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Xinxiang, China, Gao et al have observed greater risks of AR outpatients when mean temperature rose to 1.6-9.3 ˚C at a lag of 0-7 days and 23.5-28.5 ˚C at a lag of 0-3 days (Gao et al 2021). In addition to temperature range and mean temperature, two another temperature indices, interday variability (e.g., temperature variation between neighboring days) and intraday variability (e.g., diurnal temperature range (DTR)) have been assessed to examine the associations of short-term unstable weather with respiratory outcomes (Lim et al 2012;Wang et al 2020). For instance, Lim et al have reported a positive association between DTR and respiratory hospital admissions in Korea (Lim et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation